Effects of catecholamines and adrenergic-blocking agents on plasma and urinary cyclic nucleotides in man - Ball, John H. (1972)
Studies were performed in healthy volunteers to determine the effects of catecholamines and adrenergic-blocking agents on plasma and urinary levels of adenosine 3′,5′-monophosphate (cyclic AMP) and guanosine 3′,5′-monophosphate (cyclic GMP). Plasma cyclic AMP rose in response to infusions of the β-adrenergic agent, isoproterenol, or in response to infusions of either epinephrine or norepinephrine alone or in combination with the α-adrenergic-blocking agent, phentolamine. Although urinary cyclic AMP also rose, the percentage increase was less than that observed in the plasma. These treatments caused no increase in plasma cyclic GMP. Plasma cyclic GMP rose in response to infusions of α-adrenergic agents, viz., epinephrine or norepinephrine infused together with the β-blocking agent, propranolol. These treatments caused no increase in plasma cyclic AMP. These observations are consistent with the current concept that the actions of β-adrenergic agents are mediated by increases in cyclic AMP formation in target tissues. Such a mediating role has not been established for cyclic GMP, but the data suggest the possibility that cyclic GMP metabolism is responsive either to α-adrenergic stimulation or to parasympathetic stimulation which occurs as a reflexive consequence of the pressor effect of α-adrenergic agents.